Stereotactic pelvic radiotherapy with HDR boost for dose escalation in intermediate and high-risk prostate cancer (SPARE): Efficacy, toxicity and quality of life. (August 2021) - Musunuru, Hima Bindu; Cheung, Patrick; Vesprini, Danny; Liu, Stanley K.; Chu, William; Chung, Hans T.; Morton, Gerard; Deabreu, Andrea; Davidson, Melanie; Ravi, Ananth; Helou, Joelle; Ho, Ling; et al.
Highlights: SPARE is a phase II trial for intermediate and high-risk prostate cancer patients. Patients were give HDR-BT, 5 fractions of EBRT to the pelvis and hormones. Acute and late grade 3 GU toxicity was 7% and 3% with no detriment to QoL. The 5-year actuarial biochemical failure was 18.2% in this unfavorable risk cohort. Abstract: Background: The ASCO/CCO guidelines recommend brachytherapy (BT) boost for eligible intermediate- (IR) or high-risk (HR) prostate cancer (PCa) patients. We present efficacy, toxicity and quality-of-life (QoL) outcomes in patients treated on a prospective protocol of MRI dose-painted high-dose-rate BT boost (HDR-BT) followed by 5-fraction pelvic radiotherapy (RT) and 6–18 months of androgen deprivation therapy (ADT). Methods: In this phase I/II study, IR or HR PCa patients received HDR-BT 15 Gy × 1 to prostate and up to 22.5 Gy to MRI nodule, followed by 25 Gy in 5, weekly fractions to pelvis. Toxicity was assessed using CTCAEv3.0, and QoL was captured using EPIC questionnaire. Biochemical failure (BF; nadir + 2.0), and proportion of patients with PSA < 0.4 ng/ml at 4-years (4yPSARR) were evaluated. A minimally clinically important change (MCIC) was recorded if QoL score decreased >0.5 standard deviation of baseline scores. Results: Thirty-one patients (NCCN 3.2% favorable IR, 48.4% unfavorable IR and 48.4% HR) completed treatment with a median follow-up of 61 months. Median D90 to MR nodule was 19.0 Gy and median prostate V100% was 96.5%. The actuarial 5-year BF rate was 18.2%, and the 4yPSARR was 71%. One patient died of PCa. Acute grade 2 and 3 toxicities: GU: 50%, 7%, and GI: 3%, none, respectively. Late grade 2 and 3 toxicities were: GU: 23%, 3%, and GI: 7%, none, respectively. Proportion of patients with MCIC was 7.7% for urinary domain and 32.0% for bowel domain. Conclusions: This novel treatment protocol incorporating MRI dose-painted HDR-BT boost and 5-fraction pelvic RT with ADT is well tolerated.